Effect of counter-surface chemical activity on mechanochemical removal of GaAs surface. (December 2022) - Gao, Jian; Zhou, Huaicheng; Du, Junxiao; Peng, Wumao; Lin, Yu; Xiao, Chen; Yu, Bingjun; Qian, Linmao
Abstract: Using atomic force microcopy, mechanochemical removal behaviors of GaAs surface slid by Al2 O3, SiO2, and CeO2 micro-spherical tips were investigated in ambient environment. High-resolution transmission electron microscope characterization demonstrates that defect-free material removal was achieved on GaAs surface under the contact pressures much below the yield limit of plastic deformation, which can be ascribed to water-participated mechanochemical reactions. Further analysis indicates that the interfacial mechanochemical reactions are strongly affected by the counter-surface chemistry. Nano abrasive with low chemical activity inhibits the mechanochemical reaction via increasing the activation energy of the formation of interfacial bonding bridges, but there is no obvious difference in the mechanically weakening process of the activation energy for the rupture of Ga−As bond on the substrate. Highlights: Evident mechanochemical removal at the interface of GaAs/Al2 O3, GaAs/SiO2, and GaAs/CeO2 occurs in purely elastic contact. Complete lattice structure was detected beneath the wear track by HRTEM. Mechanochemical reaction mechanism on GaAs surfaces were revealed based on counter-surface chemical activity.